KEBERADAAN SALMONELLA SP. PADA SUSU OLAHAN ASAL KEDAI SUSU DI SEKITAR PERMUKIMAN MAHASISWA INSTITUT PERTANIAN BOGOR - Ulfa Apriliana Annisa; Mirnawati B Sudarwanto; Susi Soviana; Herwin Pisestyani (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
Nowadays, milk is one of the favorite drinks for Indonesian people. This relates to the awareness of society about healthy food is increasing. At the same time, there are many milk retail that are appearing. The purpose of this study was to detect the presence and level of contamination of Salmonella sp. in processed milk from milk retail around the students settlement area of ​​IPB University. In Indonesia the standard for identifying Salmonella sp. refer to Indonesian National Standard 2897: 2008. This method consists of 5 stages: pre-enrichment, enrichment, selective media planting, confirmation based on biochemical and serological tests. Milk samples in this study came from 14 milk retail in the students settlement area of the IPB University. The milk samples were taken are plain milk (milk that has not added flavor (flavorings), sugar, and ice). The selection of milk retail is taken within a radius of 2 km from the midpoint of the IPB campus in the Dramaga and Cilibende areas. Based on the results of this study, it was found that all milk samples examined showed negative results which means no Salmonella sp. contamination was found. From this study it can be concluded that the quality of processed milk sold in milk retail around the student settlement area of IPB University is good.